Medication nonadherence in children and adolescents with ADHD: results of a multicenter prospective observational study - Mechler, Konstantin; Banaschewski, Tobias; Hellenschmidt, Tobias; Correll, Christoph U.; Theisen, Frank M.; Kaess, Michael; Kölch, Michael; Libal, Gerhard; Renner, Tobias J.; Fegert, Jörg M.; Karwautz, Andreas; Plener, Paul L.; et al. (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2025)
Abstract: Objective: Attention-deficit/hyperactivity disorder (ADHD) affects 6-10 % of children and adolescents worldwide. While psychopharmacological treatments effectively reduce symptoms, incomp...
Online veröffentlicht: 23. Juni 2025
Gesehen am 02.10.2025